Preliminary Studies On Soils Of The Mirzachul Oasis And Their Classification Into Degrees Of Danger To Deflation (Journal of Pedagogical Inventions and Practices, 2023)
This article presents the results of preliminary studies conducted in the Mirzachul region (late XIX – early XX century), reducing the impact of wind erosion on the soil, monitoring various deflationary processes on irrigated lands in the region, region. The results of field experiments suggest the sowing of industrial crops between agricultural crops to restore, increase and protect the fertility of deflated soils